1994
DOI: 10.1055/s-2007-1014291
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability in Depressed Patients and Differential Effects of Paroxetine and Amitriptyline on Cardiovascular Autonomic Functions

Abstract: Twenty-four unmedicated patients with episodes of major depression (DSM-III-R) and an age- and sex-matched group of 24 normal subjects underwent a heart rate analysis. The battery of cardiovascular reflex tests included the coefficient of variation while resting (CVr) and during deep breathing (CVdr), a spectral analysis of heart rate variability, the Valsalva test, and the posture index. The depressed patients showed no significant abnormalities in any of the tests as compared to the healthy subjects. The 24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
2

Year Published

1995
1995
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(38 citation statements)
references
References 9 publications
0
36
0
2
Order By: Relevance
“…Duplicates were removed, titles and abstracts scanned, potential articles read and evaluated against inclusion criteria and authors contacted for additional data when necessary. In total, 140 case-control and 30 treatment 76,83,93,110,116,129,138,141,155,175,[187][188][189][190][191][192][193][194][195][196][197][198][199][200][201][202][203][204][205][206] studies were eligible for inclusion in the quantitative synthesis (151 case-control and 43 effect sizes for analysis); 10 of the studies were included in both the case-control and treatment analyses. 76,83,93,110,116,129,138,141,155,175 Four subgroups of disorders (mood, anxiety-related, psychotic and substance dependence disorders) and 2 classes of psychotropic medications (antidepressants and antipsychotics) were included.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Duplicates were removed, titles and abstracts scanned, potential articles read and evaluated against inclusion criteria and authors contacted for additional data when necessary. In total, 140 case-control and 30 treatment 76,83,93,110,116,129,138,141,155,175,[187][188][189][190][191][192][193][194][195][196][197][198][199][200][201][202][203][204][205][206] studies were eligible for inclusion in the quantitative synthesis (151 case-control and 43 effect sizes for analysis); 10 of the studies were included in both the case-control and treatment analyses. 76,83,93,110,116,129,138,141,155,175 Four subgroups of disorders (mood, anxiety-related, psychotic and substance dependence disorders) and 2 classes of psychotropic medications (antidepressants and antipsychotics) were included.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…Bär et al 189 Davidson et al 190 188 Dawood et al 110 Khaykin et al 191 Koschke et al 116 Lederbogen et al 192 Prasko et al 76 Rechlin 194 Rechlin 194 Rechlin et al 196 Tucker et al 83 Udupa et al 197 Udupa et al 198 Yeragani et al 201 189 Khaykin et al 191 Lederbogen et al 192 McLeod et al 193 Rechlin 194 Rechlin et al 195 Rechlin et al 195 Rechlin et al 196 Tulen et al 129 Udupa et al 198 Yeragani et al 199 Yeragani et al 200 …”
Section: Bär Et Almentioning
confidence: 99%
“…Exclusion criteria for study subjects included: (1) failure to provide a history of medical illnesses (n ¼ 3), (2) not receiving regular treatment for medical illnesses (n ¼ 17), and (3) subjects with conditions which affect cardiovascular fluctuations: an implanted cardiac pacemaker, frequent occurrence of atrial fibrillation, premature atrial or ventricular contractions, or other forms of arrhythmia (n ¼ 35). Because of the anticholinergic properties of antidepressants, it has been shown that not only treatment with tricyclic antidepressants but also selective serotonin reuptake inhibitors decreases HRV (Rechlin et al, 1994;Lederbogen et al, 2001). Due to the limited number of subjects (n ¼ 2) who took antidepressants during the study period, we excluded these two subjects as well for the sake of inadequate power as a covariate.…”
Section: Participantsmentioning
confidence: 99%
“…Chloralhydrate or zopiclon were permitted as soporifics; patients with symptoms of delusion also took the so-called atypical neurolepticum zotepin or haloperidol in lower dosages. Recently the influence of anti-depressants was critically discussed by Schnurr (1990), Rechlin et al (1994), Barg and Wolfersdorf (1996), and Barg et al (1996). It seems that with regard to electrodermal reactivity the general skin conductance level can be influenced by neurdeptics and antidepressants with a high proportion of anticholinergic side-effects, but that the rate of habituation is not affected by this.…”
Section: Study Groupmentioning
confidence: 99%